Positive electrode mixture material and lithium ion battery

JP2024026930A5Active Publication Date: 2025-01-14IDEMITSU KOSAN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022129480
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-08-16
Publication Date
2025-01-14
Estimated Expiration
2042-08-16

AI Technical Summary

Technical Problem

The low electronic conductivity and lithium ion conductivity of sulfur in positive electrodes of lithium ion batteries result in poor rate characteristics, particularly at high current densities.

Method used

A positive electrode composite material is developed, comprising a sulfide solid electrolyte, a material A with an average pore radius of 10 nm or less and a G/D ratio of 0.6 or more, and a conductive carbon material B with a high aspect ratio, where elemental sulfur is impregnated into the pores of material A, achieving a sulfur content ratio of 2.5 or more, to enhance electron and ion conductivity.

Benefits of technology

The composite material improves the rate characteristics of lithium ion batteries by ensuring uniform electron conductivity and high sulfur content, leading to enhanced energy density and discharge capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000017_0000
    Figure 00000017_0000
Patent Text Reader

Abstract

To provide a positive electrode mixture material which can increase rate characteristics of a lithium ion battery.SOLUTION: A positive mixture material includes: a sulfide solid electrolyte; a material A having electronic conductivity with an average small hole diameter of 10 nm or smaller than 10 nm; a material B as conductive carbon for which a ratio (G / D) of an area of a G-band and an area of a D-band in Laman measurement is at least 0.6; and at least one of elemental sulfur and a discharge product of the elemental sulfur in at least a part of the small holes of the material A. A ratio [S / (A+B)] of total mass (S) of the sulfur of the elemental sulfur and the discharge product of the elemental sulfur to total mass (A+B) of the materials A and B is at least 2.5.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode mixture and a lithium ion battery. [Background technology]

[0002] Regarding the electrical capacity of all-solid-state lithium-ion batteries, the use of sulfur in the positive electrode has been investigated because of its large theoretical capacity. However, sulfur has low electronic conductivity and lithium ion conductivity, which results in a problem of low discharge capacity at high current density (rate characteristics).

[0003] In order to solve the above problems, a sulfur positive electrode composite material has been developed in which activated carbon is impregnated with sulfur and then combined with a solid electrolyte (see, for example, Patent Documents 1 and 2). In addition, a positive electrode composite material has been disclosed in which a fibrous conductive assistant such as vapor grown carbon fiber (VGCF) is mixed with a compound containing sulfur (see, for example, Patent Document 3). However, there is a demand for further improvement in the rate characteristics of lithium ion batteries. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6243103 [Patent Document 2] JP 2020-161288 A [Patent Document 3] Patent Publication No. 2021-26838 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a positive electrode mixture capable of improving the rate characteristics of a lithium ion battery. [Means for solving the problem]

[0006] According to the present invention, the following positive electrode mixture and the like are provided. 1. A sulfide solid electrolyte; An electronically conductive material A having an average pore radius of 10 nm or less; Material B is a conductive carbon having a ratio of the G band area to the D band area (G / D) of 0.6 or more in Raman measurement; At least one of elemental sulfur and a discharge product of elemental sulfur present in at least a portion of the pores of the material A; A positive electrode mixture, in which the ratio [S / (A+B)] of the total mass (S) of the elemental sulfur and the discharge product of elemental sulfur to the total mass (A+B) of the materials A and B is 2.5 or more. 2. The positive electrode mixture according to 1, wherein a ratio (A:B:S) of a total mass of the material A, the material B, the elemental sulfur, and the sulfur of the discharge product of elemental sulfur is 5-15:1-10:30-50. 3. The positive electrode mixture according to 1 or 2, wherein the average pore radius of material A is less than 5 nm. 4. The positive electrode mixture according to any one of 1 to 3, wherein the material A is a porous carbon material. 5. The positive electrode mixture according to any one of 1 to 4, wherein the material B has a micropore volume of 0.1 cc / g or less. 6. The positive electrode mixture according to any one of 1 to 5, wherein the material B is carbon fiber. 7. The positive electrode mixture according to any one of 1 to 6, wherein the ratio of the area of ​​G band to the area of ​​D band (G / D) in Raman measurement of the material A is less than 0.6. 8. The positive electrode mixture according to any one of 1 to 7, wherein the total pore volume of the material A and the material B is 1.0 cc / g or more. 9. The positive electrode mixture according to any one of 1 to 8, wherein the total content of the elemental sulfur and the sulfur discharge product of the elemental sulfur is 1.0 cc or more per 1 g of the total mass of the material A and the material B. 10. The positive electrode mixture according to any one of 1 to 9, wherein the total content of the elemental sulfur and the sulfur discharge product of the elemental sulfur is 70% or more of the total pore volume of the material A and the material B. 11. A positive electrode for a lithium ion battery, comprising the positive electrode mixture according to any one of 1 to 10. A lithium ion battery comprising the positive electrode for a lithium ion battery according to 12.11. 13. A step of heating a material A having electronic conductivity and an average pore radius of 10 nm or less and elemental sulfur at a temperature equal to or higher than the melting point of the elemental sulfur to obtain a material A-elemental sulfur composite powder; The method for producing a positive electrode composite material includes a step of mixing the material A-element sulfur composite powder, a material B which is conductive carbon having a G band area / D band area of ​​0.6 or more in Raman measurement, and a sulfide solid electrolyte to obtain a positive electrode composite material. Effect of the Invention

[0007] According to the present invention, it is possible to provide a positive electrode mixture that can improve the rate characteristics of a lithium ion battery. [Brief description of the drawings]

[0008] [Figure 1] 1 is an SEM image of a cross section of the positive electrode composite material produced in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] 1. Cathode mixture A positive electrode composite according to one embodiment of the present invention includes a sulfide solid electrolyte, a material A having electronic conductivity and an average pore radius of 10 nm or less, and a material B which is conductive carbon having a ratio (G / D) of the area of ​​the G band to the area of ​​the D band in Raman measurement of 0.6 or more. At least one of elemental sulfur and a discharge product of elemental sulfur is present in at least a part of the pores of the material A, and the ratio (S / A+B) of the total mass (S) of the elemental sulfur and the discharge product of elemental sulfur in sulfur equivalent to the total mass (A+B) of the materials A and B is 2.5 or more.

[0010] In this embodiment, it is presumed that material A has the function of retaining elemental sulfur and discharge products of elemental sulfur and smoothly supplying electrons and ions by keeping the particle size of these small. On the other hand, material B has high electronic conductivity due to its high graphitization degree, which facilitates electronic conductivity to the entire positive electrode, and therefore contributes to improving the rate characteristics.

[0011] In this embodiment, the positive electrode mixture contains elemental sulfur or discharge products of elemental sulfur present in some of the pores of material A, and the ratio (S / A+B) of the total mass (S) of elemental sulfur and discharge products of elemental sulfur in sulfur equivalent to the total mass (A+B) of materials A and B is 2.5 or more. This requirement means that the amount of elemental sulfur contained in the positive electrode mixture is large, and a battery with high energy density can be obtained.

[0012] In one embodiment, the aspect ratio of material B is 5 or more. By using two kinds of materials A and B with different shapes, it is possible to uniformly impart electronic conductivity to sulfur that does not have electronic conductivity or ionic conductivity even by adding small amounts of materials A and B. In addition, since the sulfur can be maintained in a finely divided state in which lithium ions are easily supplied, it is possible to increase the content of sulfur in the positive electrode mixture and improve the rate characteristics of the battery.

[0013] It is presumed that material A has pores, and therefore elemental sulfur can be highly dispersed. On the other hand, elemental sulfur is insulating, and therefore a large content of elemental sulfur inhibits electron migration in the positive electrode. When material B has a large aspect ratio, even if the content of elemental sulfur is large, electron migration over a longer distance can be achieved compared to material A. From the above effects, it is presumed that the rate characteristics are improved in a lithium-ion battery using the positive electrode composite of this embodiment in the positive electrode. The components of this embodiment will be described below.

[0014] [Material A] Material A is not particularly limited as long as it is a material that has electronic conductivity and has pores with an average pore radius of 10 nm or less. In one embodiment, the average pore radius of the pores in material A is preferably 7 nm or less, more preferably less than 5 nm, and even more preferably 4 nm or less. The smaller the average pore radius, the greater the effect of improving the rate characteristics. The lower limit of the average pore radius of the pores in material A is not particularly limited, but is usually 0.1 nm or more.

[0015] In one embodiment, material A is preferably a porous carbon material. Preferred examples of the porous carbon material include carbon black such as Ketjen Black (registered trademark), activated carbon, Knobel (registered trademark), etc. Among these, activated carbon is preferred. These may be used alone or in combination of two or more kinds.

[0016] In one embodiment, the pore volume of material A is preferably 1.0 cc (mL) / g or more. This increases the amount of sulfur that can be retained, leading to an improvement in the energy density of the battery. The pore volume of material A is more preferably 1.5 cc / g or more, and more preferably 2.0 cc / g or more. The pore volume of electronically conductive material A is usually 10 cc / g or less.

[0017] In the present invention, the average pore radius and pore volume can be measured by the Brenauer-Emmet-Telle (BET) method or the BJH method (Barrett-Joyner-Halenda method). Specifically, the nitrogen adsorption isotherm can be obtained by adsorbing nitrogen gas to the electron conductive material A at the liquid nitrogen temperature. The measurement can be performed using, for example, a specific surface area / pore distribution measuring device (Autosorb-3) manufactured by Quantacrome.

[0018] [Elemental sulfur] The elemental sulfur (sulfur) is not particularly limited, but preferably has a purity of 95% by mass or more, more preferably 96% by mass or more, and particularly preferably 97% by mass or more. Examples of the crystal system of elemental sulfur include α-sulfur (orthorhombic system), β-sulfur (monoclinic system), γ-sulfur (monoclinic system), and amorphous sulfur. These may be used alone or in combination of two or more. Elemental sulfur becomes molten liquid when heated.

[0019] During the battery reaction, part or all of the elemental sulfur is converted into a discharge product. Therefore, in one embodiment, a discharge product of elemental sulfur is present in the positive electrode mixture (positive electrode). When a discharge product is present, the amount of sulfur contained in the positive electrode mixture is the total amount of elemental sulfur and sulfur contained in the discharge product. Examples of discharge products of elemental sulfur include Li2S in a fully discharged state and lithium polysulfides in intermediate stages such as Li2S2, Li2S4, Li2S6, and Li2S8.

[0020] In the positive electrode composite, part or all of the elemental sulfur is impregnated into the pores of material A. The elemental sulfur that is not impregnated into the pores is present so as to cover part or all of materials A and B. Whether or not sulfur is impregnated into the pores of material A can be confirmed by analyzing the particle cross section of material A using an analytical method capable of element mapping such as SEM-DES or TEM-EDX, and evaluating the overlap of elements derived from material A and sulfur elements. In one embodiment, the positive electrode composite material contains a large amount of elemental sulfur, so that elemental sulfur is present outside the pores of material A. In this case, the composite of elemental sulfur and material A becomes a pellet-like lump, but it can be turned into powder by mechanically crushing it.

[0021] [Material B] Material B is a conductive carbon, and the ratio of the area of ​​the G band to the area of ​​the D band (G / D) in Raman measurement, which indicates the degree of graphitization of the carbon material, is 0.6 or more. The area of ​​the G band is 1800 cm -1 ~1475cm -1 and the area of ​​the D band is 1475 cm -1 ~700cm -1The area of ​​the D band indicates the amount of defects in the carbon material. A carbon material having the ratio (G / D) of 0.6 or more is expected to have high electrical conductivity because of the progress of graphitization. The ratio (G / D) is preferably 0.7 or more, more preferably 1.0 or more, 1.5 or more, and even more preferably 2.0 or more. In graphite with no defects, the ratio (G / D) is infinite because there is no D band, but it is usually 100 or less, and preferably 10 or less. The G band area and the D band area in the Raman measurement are measured by the method described in the Examples.

[0022] In one embodiment, the ratio (G / D) of material A in Raman measurement is less than 0.6, and preferably less than 0.55. A ratio of less than 0.6 means that material A has a moderate defect structure, and Li ion conduction in the material through the defects can be expected. It can also be expected that sulfur will be easily impregnated from the defects. For example, in carbon materials that do not have a graphite structure, such as diamond, the G band is not produced, so the ratio (G / D) is 0, but as a conductive material, a ratio of 0.1 or more is preferable, and 0.2 or more is even more preferable. By being 0.1 or more, a moderately developed graphite structure is contained in material A, and suitable electronic conductivity is obtained.

[0023] In one embodiment, the aspect ratio of material B is 5 or more, preferably 10 or more, and more preferably 15 or more. The higher the aspect ratio, the smaller the amount of material that can impart electronic conductivity to the entire electrode. The aspect ratio of material B is preferably 5000 or less, more preferably 3000 or less, and even more preferably 2000 or less. If the aspect ratio is too high, the bulk density of the powder decreases, the transportation cost increases, and the mixability decreases.

[0024] The aspect ratio of material B is calculated by the following formula: Aspect ratio of material B = average fiber length of material B / average fiber diameter of material B The aspect ratio is evaluated using a method appropriate for the size of the material, for example, a scanning electron microscope (SEM).

[0025] Carbon fibers are preferred as material B. Examples of carbon fibers include carbon nanotubes and vapor grown carbon fibers (VGCF). In addition, acetylene black, Denka Black (registered trademark), thermal black, channel black, etc., which have a structure and function as a conductive assistant with a substantially high aspect ratio, and graphene, reduced graphene, flake graphite, etc., which are flat electron conductors, can also be used as material B. These may be used alone or in combination of two or more.

[0026] The average fiber length of material B is preferably 3 μm or more, more preferably 5 μm or more. The average fiber length of material B is preferably 500 μm or less, more preferably 100 μm or less. By adjusting the average fiber length in this manner, electronic conductivity can be imparted to the entire electrode with a small amount of material.

[0027] The average fiber diameter of material B is preferably 2 nm or more, more preferably 5 nm or more. The average fiber diameter of material B is preferably 1000 nm or less, more preferably 300 nm or less. By adjusting the average fiber diameter in this manner, electronic conductivity can be maintained sufficiently, and electronic conductivity can be imparted to the entire electrode even with a small amount of material mixed.

[0028] In one embodiment, the amount of micropores in material B is 0.1 cc / g or less. Here, micropores generally mean pores with a pore diameter of 2 nm or less. When the amount of micropores is 0.1 cc / g, material B is considered to have substantially no micropores. It is more preferable that the amount of micropores in material B is 0.05 cc / g or less. Since material B does not have pores inside, it has high electronic conductivity, and therefore a small amount of material B can impart electronic conductivity to the entire positive electrode. The amount of micropores can be analyzed using t-plot from the nitrogen adsorption isotherm of material B. In addition, the absence of micropores containing sulfur can also be analyzed by evaluating the presence or absence of particles with no overlap of C and S using analytical methods capable of elemental mapping such as SEM-EDS and TEM-EDX.

[0029] [Sulfide solid electrolyte] The sulfide solid electrolyte is a solid electrolyte that contains at least sulfur atoms and exhibits ionic conductivity due to the metal atoms contained therein, and contains, in addition to sulfur atoms, preferably lithium atoms and phosphorus atoms, more preferably lithium atoms, phosphorus atoms and halogen atoms, and has ionic conductivity due to lithium atoms. The sulfide solid electrolyte may be an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte.

[0030] (Amorphous sulfide solid electrolyte) As the amorphous sulfide solid electrolyte, any one that contains at least sulfur atoms and exhibits ionic conductivity due to the metal atoms contained therein can be used without any particular limitation. Representative examples include solid electrolytes containing sulfur atoms, lithium atoms, and phosphorus atoms, such as Li2S-P2S5, which are composed of lithium sulfide and phosphorus sulfide; solid electrolytes composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr; and solid electrolytes further containing other elements such as oxygen and silicon, such as Li2S-P2S5-Li2O-LiI and Li2S-SiS2-P2S5-LiI. From the viewpoint of obtaining higher ionic conductivity, a solid electrolyte composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, or Li2S-P2S5-LiI-LiBr, is preferred. The types of elements constituting the amorphous sulfide solid electrolyte can be confirmed, for example, by an ICP emission spectroscopic analyzer.

[0031] When the amorphous sulfide solid electrolyte contains at least Li2S-P2S5, the molar ratio of Li2S to P2S5 is preferably 30-85:15-70, more preferably 40-80:20-60, and even more preferably 45-78:22-55, from the viewpoint of obtaining high chemical stability and higher ionic conductivity. When the amorphous sulfide solid electrolyte is, for example, Li2S-P2S5-LiI-LiBr, the total content of lithium sulfide and diphosphorus pentasulfide is preferably 30 to 95 mol%, more preferably 35 to 90 mol%, and even more preferably 40 to 85 mol%. The ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, more preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%.

[0032] In the case where the amorphous sulfide solid electrolyte contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, the compounding ratio (molar ratio) of these atoms is preferably 1.0-1.8:1.0-2.0:0.1-0.8:0.01-0.6, more preferably 1.1-1.7:1.2-1.8:0.2-0.6:0.05-0.5, and still more preferably 1.2-1.6:1.3-1.7:0.25-0.5:0.08-0.4. In addition, when bromine and iodine are used in combination as halogen atoms, the compounding ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms, bromine atoms, and iodine atoms is preferably 1.0-1.8:1.0-2.0:0.1-0.8:0.01-0.3:0.01-0.3, more preferably 1.1-1.7:1.2-1.8:0.2-0.6:0.02-0.25:0.02-0.25, more preferably 1.2-1.6:1.3-1.7:0.25-0.5:0.03-0.2:0.03-0.2, and even more preferably 1.35-1.45:1.4-1.7:0.3-0.45:0.04-0.18:0.04-0.18. By setting the compounding ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms within the above range, it becomes easier to obtain a solid electrolyte having a thiolithiregion II type crystal structure described below and having higher ion conductivity.

[0033] The shape of the amorphous sulfide solid electrolyte is not particularly limited, but may be, for example, particulate. The average particle diameter (D 50 ) can be, for example, in the range of 0.01 μm to 500 μm, or 0.1 to 200 μm. In this specification, the average particle size (D 50 ) is the particle size at which the particle size distribution curve is accumulated from the smallest particle to the largest particle size, and the volume distribution is the average particle size that can be measured using, for example, a laser diffraction / scattering particle size distribution measuring device.

[0034] (Crystalline sulfide solid electrolyte) The crystalline sulfide solid electrolyte may be, for example, a so-called glass ceramic obtained by heating the above-mentioned amorphous sulfide solid electrolyte to a crystallization temperature or higher, and a sulfide solid electrolyte having the following crystal structure may be used. Examples of the crystal structure that the crystalline sulfide solid electrolyte containing lithium atoms, sulfur atoms, and phosphorus atoms may have include a Li3PS4 crystal structure, a Li4P2S6 crystal structure, a Li7PS6 crystal structure, a Li7P3S 11 Examples of such structures include a crystal structure having peaks at 2θ=approximately 20.2° and 23.6° (for example, JP 2013-16423 A).

[0035] In addition, the crystalline sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms can have a crystal structure such as Li 4-x Ge 1-x P x S4 thio-LISICON Region II crystal structure (Kanno et al., Journal of The Electrochemical Society, 148(7)A742-746(2001)), Li 4-x Ge 1-x P xExamples of the crystal structure include those similar to the S4 thio-LISICON Region II type (see Solid State Ionics, 177 (2006), 2721-2725). Here, the "thio-LISICON Region II type crystal structure" refers to Li 4-x Ge 1-x P x S4 thio-LISICON Region II crystal structure, Li 4-x Ge 1-x P x This indicates that the crystal structure is similar to that of the S4 thio-LISICON Region II type.

[0036] In X-ray diffraction measurements using CuKα radiation, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ = 17.5°, 18.3°, 26.1°, 27.3°, and 30.0°, the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ = 16.9°, 27.1°, and 32.5°, the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ = 15.3°, 25.2°, 29.6°, and 31.0°, and the diffraction peaks of the Li7P3S 11 Diffraction peaks of the crystal structure appear, for example, at 2θ = 17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°. 4-x Ge 1-x P x The diffraction peaks of the S4 thio-LISICON Region II crystal structure appear, for example, at 2θ = 20.1°, 23.9°, and 29.5°, and Li 4-x Ge 1-x P x Diffraction peaks of a crystal structure similar to S4 thio-LISICON Region II type appear, for example, at 2θ=20.2° and 23.6°. Note that these peak positions may vary within a range of ±0.5°.

[0037] In addition, as the crystal structure of the crystalline sulfide solid electrolyte, an argyrodite-type crystal structure can also be mentioned. As the argyrodite-type crystal structure, for example, the Li7PS6 crystal structure; the composition formula Li having the structural framework of Li7PS6 7-x P 1-y Si y S6 and Li 7+x P 1-y Si y S6 (x is -0.6 to 0.6, y is 0.1 to 0.6); the crystal structure represented by Li 7-x-2y PS 6-x-y Cl x (0.8 ≦ x ≦ 1.7, 0 < y ≦ -0.25x + 0.5); the crystal structure represented by Li 7-x PS 6-x Ha x (Ha is Cl or Br, x is preferably 0.2 to 1.8) can be mentioned.

[0038] Among the above crystal structures, as the crystal structure of the crystalline sulfide solid electrolyte, the Li3PS4 crystal structure, the thio-Lisicon region II-type crystal structure, and the argyrodite-type crystal structure are preferable.

[0039] The shape of the crystalline sulfide solid electrolyte is not particularly limited, and for example, particulate form can be mentioned. The average particle diameter (D 50 ) of the particulate crystalline sulfide solid electrolyte is, similar to the average particle diameter (D 50 ) of the aforementioned amorphous sulfide solid electrolyte, for example, within the range of 0.01 μm to 500 μm, 0.1 to 200 μm can be exemplified.

[0040] [Mixing ratio] In the positive electrode composite material of the present embodiment, the content of material B is preferably 20 to 200 parts by mass, more preferably 30 to 100 parts by mass when the amount of material A is 100 parts by mass. By satisfying the above range, the conductivity within the positive electrode composite material can be maintained high, and the rate characteristics are likely to be improved.

[0041] In addition, the ratio [S / (A+B)] of the total mass (S) of elemental sulfur and discharge products of elemental sulfur in sulfur equivalent to the total mass (A+B) of materials A and B is 2.5 or more. The ratio [S / (A+B)] is preferably 3 or more. In the positive electrode mixture, the higher the ratio of elemental sulfur is, the higher the energy density of the battery can be expected to be if the utilization rate of sulfur is the same. On the other hand, since it becomes difficult to provide sufficient electronic conduction in the positive electrode, the ratio [S / (A+B)] is preferably 10 or less, and more preferably 5 or less.

[0042] The mass ratio (A:B:S) of material A, material B, and the total mass (S) of elemental sulfur and discharge products of elemental sulfur in terms of sulfur is preferably 5-15:1-10:30-50, more preferably 5-10:2-8:35-45, and particularly preferably 7-10:3-8:35-45. This allows the effect of improving the efficiency of ionic conduction and electronic conduction by filling the pores of material A with sulfur and retaining it as small particles, and the effect of material B imparting electronic conductivity to the entire electrode to function in a well-balanced manner, resulting in good battery characteristics.

[0043] The content of the sulfide solid electrolyte is preferably 5 to 200 parts by mass, and more preferably 10 to 120 parts by mass, when the total of material A, material B, and elemental sulfur is 100 parts by mass. If the content of the solid electrolyte is 5 parts by mass or less, it becomes difficult to obtain sufficient ion conduction, and if the solid electrolyte is contained in an amount of 200 parts by mass or more, the content of the active material decreases, making it difficult to improve the energy density.

[0044] In one embodiment, the total content of elemental sulfur and discharge products of elemental sulfur in the positive electrode composite in sulfur equivalent is preferably 1.0cc or more, more preferably 1.5cc or more, and even more preferably 2.0cc or more per 1g of the total of materials A and B. The total content of elemental sulfur and discharge products of elemental sulfur in sulfur equivalent is preferably 10cc or less, more preferably 5.0cc or less, and even more preferably 4.0cc or less per 1g of the total of materials A and B. By setting it in the above range, the content of elemental sulfur becomes sufficient, and the rate characteristics are easily improved. For the purposes of conversion, the density of elemental sulfur is assumed to be 2 g / cc.

[0045] In one embodiment, the total content of elemental sulfur and discharge products of elemental sulfur in the positive electrode composite in terms of sulfur is preferably 70% or more of the total pore volume of material A and material B, more preferably 100% or more, and even more preferably 120% or more. This ensures a sufficient content of elemental sulfur, resulting in a high energy density. The total content of elemental sulfur and discharge products of elemental sulfur in terms of sulfur is preferably 300% or less of the total pore volume of material A and material B, more preferably 200% or less, and even more preferably 170% or less. The total pore volume of material A and material B can be calculated from the amounts (g) of materials A and B charged and the above-mentioned pore volumes (cc / g).

[0046] In one embodiment, the positive electrode mixture may or may not contain other components other than the sulfur-based active material, the solid electrolyte, and the conductive additive. The other components are not particularly limited, but may include, for example, a binder, a solvent, and a dispersant. The positive electrode mixture of this embodiment can be produced, for example, by the production method of the present invention described below.

[0047] 2. Manufacturing method of the positive electrode mixture A method for producing a positive electrode mixture according to one embodiment of the present invention includes the following steps (1) and (2). Step (1): A step of heating an electronically conductive material A having an average pore radius of 10 nm or less and elemental sulfur at a temperature equal to or higher than the melting point of the elemental sulfur to obtain a material A-elemental sulfur composite powder. Step (2): A step of mixing material A-element sulfur composite powder, material B which is conductive carbon having a G band area / D band area of ​​0.6 or more in Raman measurement, and a sulfide solid electrolyte to prepare a positive electrode composite material.

[0048] [Process (1)] In step (1), for example, material A and elemental sulfur are mixed and sealed, and then the mixture is heated to melt the elemental sulfur and impregnate the elemental sulfur into the pores, thereby producing a material A-elemental sulfur composite powder.

[0049] In the step (1), the mixing ratio of the material A and the elemental sulfur can be appropriately adjusted according to the materials used. In one embodiment, as described above, the content of elemental sulfur is preferably 1.0 cc or more per 1 g of material A. In addition, the content of elemental sulfur is preferably 10 cc or less per 1 g of material A. In one embodiment, the content of elemental sulfur is preferably 70% or more of the total pore volume of material A. Also, it is preferably 300% or less of the total pore volume.

[0050] A mixture of material A and elemental sulfur is heated at a temperature equal to or higher than the melting point of elemental sulfur (about 115°C). The heating temperature is adjusted according to material A and elemental sulfur, but is preferably equal to or higher than 130°C, and more preferably equal to or higher than 150°C. The upper limit of the heating temperature is equal to or lower than the boiling point of elemental sulfur (about 445°C). The heating time is preferably 0.1 to 24 hours. After heating, the mixture is cooled to obtain a composite powder of material A and elemental sulfur. If necessary, a pulverization step may be carried out after cooling.

[0051] [Process (2)] In step (2), material A-element sulfur composite powder, material B which is conductive carbon having a G band area / D band area ratio of 0.6 or more in Raman measurement, and a sulfide solid electrolyte are mixed to obtain a positive electrode composite. For example, after the above step (1), material A-element sulfur composite powder and material B are mixed by applying mechanical stress to obtain a positive electrode composite material. Here, "applying mechanical stress" means mechanically applying shear force, impact force, etc. Examples of means for applying mechanical stress include a pulverizer such as a planetary ball mill, a vibration mill, a tumbling mill, and a kneader. Materials A and B may be partially pulverized by this step.

[0052] In one embodiment, the blending amount of material B is preferably 20 to 200 parts by mass with respect to 100 parts by mass of material A, as described above. The amount of the sulfide solid electrolyte mixed is preferably 5 to 200 parts by mass per 100 parts by mass of the total of material A, material B, and elemental sulfur.

[0053] As mixing conditions, for example, when a planetary ball mill is used, the rotation speed may be several tens to several hundreds of revolutions per minute, and the processing time may be 0.5 to 100 hours. More specifically, in the case of the planetary ball mill (manufactured by Fritsch: model number P-5) used in the examples of the present application, the rotation speed of the planetary ball mill is preferably 100 rpm or more and 600 rpm or less, and more preferably 150 rpm or more and 400 rpm or less. When balls serving as grinding media are used, for example, zirconia balls, their diameter is preferably 0.2 to 20 mm.

[0054] In one embodiment, the positive electrode mixture can be produced by mixing the above-mentioned material A-element sulfur composite powder and material B, and then adding a sulfide solid electrolyte and mixing again.

[0055] In one embodiment, the positive electrode mixture may be heated after the step of mixing the material A-element sulfur composite powder with the material B. The solid electrolyte, the crystallinity of which has been reduced in the mixing step, may be recrystallized or heated to form an interface, thereby improving the ion conductivity and improving the battery characteristics.

[0056] The heating temperature and time can be adjusted as appropriate depending on the type of solid electrolyte, but for example, when the crystallization temperature of the solid electrolyte is 200° C. or lower, the heat treatment is performed according to the crystallization temperature of the solid electrolyte. When the intercrystalline temperature of the solid electrolyte is high, such as 300° C. or higher, heating at about 200° C., where excessive sulfur evaporation does not occur, can reform the interface, although it does not lead to crystallization.

[0057] The heating temperature is not limited because it varies depending on the type of solid electrolyte as described above, but is, for example, 250°C or less, preferably 200°C or less. The lower the temperature, the more the evaporation of sulfur can be suppressed. The heating temperature is 50°C or more, preferably 100°C or more, and more preferably 120°C or more. The heating time is not particularly limited, but is, for example, 1 minute to 99 hours, preferably 10 minutes to 10 hours, and particularly preferably 30 minutes to 3 hours.

[0058] The timing of heating may be immediately after the composite is formed, or the composite may be processed into an electrode sheet by a method such as slurry casting using a solvent or electrostatic coating, and then heating may be performed. In the case of production by slurry casting, it is also possible to reduce the number of steps by performing heating for crystallization simultaneously with removing the solvent.

[0059] 3. Lithium-ion battery A lithium ion battery according to an embodiment of the present invention includes the above-mentioned cathode composite of the present invention. For example, an all-solid-state lithium ion battery can be manufactured by using a solid electrolyte instead of a liquid electrolyte. By using the cathode composite of the present invention, an all-solid-state lithium ion battery with good rate characteristics can be manufactured.

[0060] An all-solid-state lithium ion battery mainly consists of a positive electrode layer, a negative electrode layer, and an electrolyte layer, and the positive electrode mixture of the present invention is suitable as a constituent material of the positive electrode layer. The negative electrode layer and the electrolyte layer can be manufactured by a known method. In addition to the positive electrode layer, the negative electrode layer, and the electrolyte layer, it is preferable to use a current collector, and a known current collector is also used. The solid electrolyte is not particularly limited, but examples thereof include the sulfide solid electrolytes described above. EXAMPLES

[0061] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The ratio of the area of ​​the G band to the area of ​​the D band (G / D) in the Raman measurements of materials A and B was determined under the following conditions. <Measurement conditions> Equipment: DXR2 (Thermo Fisher Scientific Co., Ltd.) Exposure time: 10 seconds Number of times: 20 Background: 20 times Laser wavelength: 532nm Laser power: 3.0mW Pinhole: 25μm pinhole Resolution:HIGH RES GRATING Measurement range: 50~1800cm -1 Measurement magnification: 50x objective lens

[0062] 700 and 1800 cm -1 The straight line passing through two points with no peaks due to nearby structures was used as the baseline. If there is a peak at the above wavenumber, a wavenumber with no nearby peaks can be used as the starting point of the baseline. 1475cm separating G and D bands -1 1400~1550cm -1 The wave numbers at which the respective Raman spectra had their minimum values ​​were calculated, and the average value was used.

[0063] Example 1 (1) Preparation of activated carbon-element sulfur composite powder Activated carbon (MSC-30, manufactured by Kansai Thermochemical Co., Ltd., pore volume 1.67 cc / g, average pore radius 1.12 nm) and elemental sulfur were placed in a glass bottle in a mass ratio of 1:5 as material A, and the bottle was sealed in a SUS tube container. The mixture was heated in an electric furnace at 150°C for 6 hours and at 300°C for 2.75 hours to obtain an activated carbon-elemental sulfur composite powder. The pore volume of the activated carbon is 1.67cc / g, and assuming the density of elemental sulfur is 2g / cc, the content of elemental sulfur per 1g of activated carbon is 2.5cc. From the above, the content (charged amount) of elemental sulfur is 150% (volume) of the total pore volume of the activated carbon. Cross-sections of the activated carbon-elemental sulfur composite powder were prepared by ion milling, and the cross-sections were observed using SEM-EDS. As a result, elemental sulfur was observed within the carbon, confirming that elemental sulfur had permeated the pores of the activated carbon. The average pore radius and pore volume of the activated carbon were measured using a pore distribution measuring device (Autosorb-3) manufactured by Quantacrome.

[0064] (2) Preparation of solid electrolyte 0.4127g of lithium sulfide, 0.6655g of diphosphorus pentasulfide, 0.2137g of lithium iodide, 0.2080g of lithium bromide, and 10 zirconia balls with a diameter of 10 mm were placed in a 45mL zirconia pot and sealed. The mixture was mixed (mechanical milled) for 40 hours at a rotation speed of 370 rpm using a planetary ball mill (Fritsch, model number P-7) to obtain a powder. The obtained powder was heated at 195°C for 3 hours to obtain a solid electrolyte.

[0065] (3) Preparation of positive electrode mixture 0.45 g of the activated carbon-element sulfur composite powder obtained in (1) above, 0.5 g of the solid electrolyte obtained in (2) above, and 0.05 g of vapor-grown multi-walled carbon nanotubes (VGCF (registered trademark), manufactured by Showa Denko K.K., average fiber length 6 μm, average fiber diameter 150 nm, aspect ratio 40, micropore amount by t-plot method 0 cc / g) were placed in a 45 mL zirconia pot together with 10 zirconia balls having a diameter of 10 mm and sealed (material A + material B: sulfur = 1:3 (mass ratio), material A: material B: sulfur = 7.5:5:37.5 (mass ratio)). Using a planetary ball mill (manufactured by Fritsch, model number P-7), mixing was carried out at a rotation speed of 370 rpm for 20 hours at room temperature to obtain a powder of a positive electrode mixture.

[0066] (4) Fabrication of all-solid-state lithium-ion batteries 100 mg of the solid electrolyte prepared in (2) above was placed in a Macol (registered trademark) cylinder with a diameter of 10 mm and pressure molded. The positive electrode composite powder prepared in (3) above was placed on the pressurized surface so that the content of elemental sulfur was 1.75 mg, and pressure molded again. Indium foil and lithium foil were placed on the pressurized surface opposite to the positive electrode composite, and pressure was applied to produce an all-solid-state battery.

[0067] Example 2 A positive electrode composite powder was obtained in the same manner as in Example 1, except that the activated carbon (MSC-30) in Example 1 was changed to a porous carbon material (CNovel (registered trademark), manufactured by Toyo Tanso Co., Ltd., pore volume 3.09 cc / g, average pore radius 4.27 nm). The content of elemental sulfur accounts for 81% of the total pore volume. As a result of observing a cross section of the porous carbon material-elemental sulfur composite powder by SEM-EDS in the same manner as in Example 1, it was confirmed that elemental sulfur was impregnated into the pores of the porous carbon material. An all-solid-state battery was produced in the same manner as in Example 1, except that the obtained positive electrode composite powder was used.

[0068] Example 3 A positive electrode composite powder was obtained in the same manner as in Example 1, except that the activated carbon (MSC-30) in Example 1 was changed to carbon black (Ketjen Black (registered trademark), KB, pore volume 4.33 cc / g, average pore radius 6.64 nm). The content of elemental sulfur was 58% of the pore volume. As a result of observing the cross section of the carbon black-elemental sulfur composite powder by SEM-EDS in the same manner as in Example 1, it was confirmed that elemental sulfur was impregnated into the pores of the carbon black. An all-solid-state battery was produced in the same manner as in Example 1, except that the obtained positive electrode composite powder was used.

[0069] Comparative Example 1 In Example 1 (3), 0.5 g of activated carbon-element sulfur composite powder, 0.5 g of solid electrolyte, and 10 zirconia balls having a diameter of 10 mm were placed in a zirconia pot without adding vapor-grown multi-walled carbon nanotubes (VGCF (registered trademark)). A positive electrode composite powder was obtained in the same manner as in Example 1 (material A + material B: sulfur = 1: 5 (mass ratio), material A: material B: sulfur = 8.3: 0: 41.7 (mass ratio)). A solid-state battery was produced in the same manner as in Example 1, except that the obtained positive electrode composite powder was used.

[0070] Comparative Example 2 In Example 1 (3), the activated carbon-element sulfur composite powder was not used, and 0.125 g of VGCF, 0.375 g of sulfur, 0.5 g of solid electrolyte, and 10 zirconia balls having a diameter of 10 mm were placed in a zirconia pot in the same manner as in Example 1 to obtain a positive electrode composite powder (material A + material B: sulfur = 1: 3 (mass ratio), material A: material B: sulfur = 0: 12.5: 37.5 (mass ratio)). A solid-state battery was produced in the same manner as in Example 1, except that the obtained positive electrode composite powder was used.

[0071] Comparative Example 3 In Example 1 (3), the activated carbon-element sulfur composite powder was not used, and 0.075 g of acetylene black (AB, carbon material without pores, Denka Black Granules manufactured by Denka Co., Ltd.), 0.050 g of VGCF, 0.375 g of sulfur, and 10 zirconia balls with a diameter of 10 mm were put into a zirconia pot, but the same procedure was followed as in Example 1 to obtain a positive electrode composite powder (material A + material B: sulfur = 1: 3 (mass ratio), material A: material B: sulfur = 0: 12.5: 37.5 (mass ratio)). A solid-state battery was produced in the same manner as in Example 1, but the obtained positive electrode composite powder was used.

[0072] Comparative Example 4 A carbon black-sulfur composite powder was prepared in the same manner as in Example 1(1), except that the activated carbon (MSC-30) was replaced with carbon black (Ketjen Black (registered trademark), KB, pore volume 4.33 cc / g, average pore radius 6.64 nm). The content of elemental sulfur was 58% of the total pore volume. In Example 1 (3), a positive electrode mixture powder was obtained in the same manner as in Example 1 (3), except that vapor-grown multi-walled carbon nanotubes (VGCF (registered trademark)) were not added, and 0.5 g of carbon black-element sulfur composite powder, 0.5 g of solid electrolyte, and 10 zirconia balls having a diameter of 10 mm were placed in a zirconia pot (material A + material B: sulfur = 1: 5 (mass ratio), material A: material B: sulfur = 8.3: 0: 41.7 (mass ratio)). A solid-state battery was produced in the same manner as in Example 1, except that the obtained positive electrode mixture powder was used.

[0073] Example 4 In Example 1 (3), instead of vapor-grown multi-walled carbon nanotubes (VGCF (registered trademark)), 0.05 g of acetylene black (AB, carbon material without pores, Denka Black granular manufactured by Denka Co., Ltd., micropore amount 0cc / g by t-plot method), 0.45 g of activated carbon-element sulfur composite powder, 0.5 g of solid electrolyte, and 10 zirconia balls with a diameter of 10 mm were put into a zirconia pot, and a positive electrode mixture powder was obtained in the same manner (material A + material B: sulfur = 1: 3 (mass ratio), material A: material B: sulfur = 7.5: 5: 37.5 (mass ratio)). A solid-state battery was produced in the same manner as in Example 1, except that the obtained positive electrode mixture powder was used. Acetylene black is said to have a structure in which carbon particles without pores are connected, and the same effect as adding carbon with a high aspect ratio can be expected.

[0074] Example 5 In Example 1 (3), instead of vapor-grown multi-walled carbon nanotubes (VGCF (registered trademark)), 0.05 g of carbon nanofibers (Merck Co., Ltd., Carbon nanofibers, width 100 nm, length 20-200 μm, nominal aspect ratio 200-2000, PR-25-XT-HHT, micropore amount 0 cc / g by t-plot method), 0.45 g of activated carbon-element sulfur composite powder, 0.5 g of solid electrolyte, and 10 zirconia balls with a diameter of 10 mm were put into a zirconia pot, and a positive electrode mixture powder was obtained in the same manner (material A + material B: sulfur = 1: 3 (mass ratio), material A: material B: sulfur = 7.5: 5: 37.5 (mass ratio)). A solid-state battery was produced in the same manner as in Example 1, except that the obtained positive electrode mixture powder was used.

[0075] Example 6 In Example 1 (3), 0.025 g of vapor-grown multi-walled carbon nanotubes (VGCF (registered trademark)), 0.475 g of activated carbon-element sulfur composite powder, 0.5 g of solid electrolyte, and 10 zirconia balls having a diameter of 10 mm were placed in a zirconia pot, but the same procedure was followed to obtain a positive electrode composite powder (material A + material B: sulfur = 1: 3.2 (mass ratio), material A: material B: sulfur = 9.5: 2.5: 38 (mass ratio)). Except for using the obtained positive electrode composite powder, an all-solid-state battery was produced in the same manner as in Example 1.

[0076] (evaluation) [Scanning Microscope (SEM)] Fig. 1 is an SEM image of the positive electrode mixture obtained in Example 1(3). It was confirmed that VGCF was well dispersed in the positive electrode mixture.

[0077] [Evaluation of battery characteristics] A constant current charge / discharge test was performed on the all-solid-state batteries prepared in each example. The cutoff potential of the constant current test was set to 0.8-2.2 V vs. Li-In, and the current density was set as shown in Table 1.

[0078] [Table 1]

[0079] Table 2 shows the physical properties of Materials A and B. Table 3 shows the discharge capacity (mAh / g) per gram of sulfur in the second cycle (current density during discharge: 0.147 mA) and the fifth cycle (current density during discharge: 0.586 mA) for Examples 1 to 6 and Comparative Examples 1 to 4.

[0080] [Table 2]

[0081] [Table 3]

[0082] From Table 3, it can be confirmed that when materials A and B are used in combination as in the examples, the discharge capacity is large and the rate characteristics are excellent. It can also be confirmed that the presence or absence of pores in material A affects the rate characteristics. It can also be confirmed that even when the type and content of material B are changed, the discharge capacity is larger and the rate characteristics are excellent than those of comparative examples 1 and 2. [Industrial Applicability]

[0083] The positive electrode mixture of the present invention is suitable for the positive electrode of a lithium ion battery. The lithium ion battery of the present invention is suitable for use in, for example, information-related devices and communication devices such as personal computers, video cameras, and mobile phones, and vehicles such as electric vehicles.

Claims

1. A sulfide solid electrolyte; An electronically conductive material A having an average pore radius of 10 nm or less; Material B is a conductive carbon having a ratio of the area of ​​the G band to the area of ​​the D band (G / D) of 0.6 or more in Raman measurement; At least one of elemental sulfur and a discharge product of elemental sulfur present in at least a portion of the pores of the material A; The ratio [S / (A + B)] of the total mass (S) of the elemental sulfur and the discharge product of elemental sulfur to the total mass (A + B) of the materials A and B is 2.5 or more. A positive electrode mixture.

2. The ratio (A:B:S) of the total mass of the material A, the material B, and the elemental sulfur and the discharge product of elemental sulfur is 5 to 15: 1 to 10: 30 to 50. The positive electrode mixture according to claim 1.

3. 2. The cathode composite of claim 1, wherein the average pore radius of material A is less than 5 nm.

4. The positive electrode mixture according to claim 1 , wherein the material A is a porous carbon material.

5. 2. The positive electrode composite according to claim 1, wherein the micropore volume of material B is 0.1 cc / g or less.

6. 2. The positive electrode composite of claim 1, wherein material B is carbon fiber.

7. The positive electrode composite material according to claim 1, wherein the ratio of the area of ​​the G band to the area of ​​the D band (G / D) in Raman measurement of the material A is less than 0.

6.

8. 2. The positive electrode mixture according to claim 1, wherein the total pore volume of said material A and said material B is 1.0 cc / g or more.

9. The positive electrode mixture according to claim 1, wherein the total content of the elemental sulfur and the sulfur discharge product of the elemental sulfur is 1.0 cc or more per 1 g of the total mass of the material A and the material B.

10. 2. The positive electrode mixture according to claim 1, wherein the total content of the elemental sulfur and the sulfur discharge product of the elemental sulfur is 70% or more of the total pore volume of the material A and the material B.

11. A positive electrode for a lithium ion battery comprising the positive electrode mixture according to any one of claims 1 to 10.

12. A lithium ion battery comprising the positive electrode for a lithium ion battery according to claim 11.

13. A step of heating a material A having electronic conductivity and an average pore radius of 10 nm or less and elemental sulfur at a temperature equal to or higher than the melting point of the elemental sulfur to obtain a material A-elemental sulfur composite powder; The method for producing a positive electrode composite material includes a step of mixing the material A-element sulfur composite powder, a material B which is conductive carbon having a G band area / D band area of ​​0.6 or more in Raman measurement, and a sulfide solid electrolyte to obtain a positive electrode composite material.